Identification of a dietary pattern prospectively associated with increased adiposity during childhood and adolescence. - Ambrosini, G; Emmett, P; Northstone, K; Howe, L; Tilling, K; Jebb, SA (2012)
BACKGROUND: Specific dietary risk factors for excess adiposity in young people are poorly understood. However, studies in adults suggest dietary energy density, fat and fibre are critical dietary factors. OBJECTIVE: To examine longitudinal relationships between a dietary pattern (DP) characterised by dietary energy density, % total energy from fat and fibre density and fat mass (FM) in children from 7 to 15 years of age. DESIGN: Subjects were 6772 children from the UK Avon Longitudinal Study of Parents and Children. Dietary intake was assessed using a 3-day food diary at 7, 10 and 13 years of age. An energy-dense, high-fat, low-fibre DP was identified using reduced rank regression and subjects scored for the DP at each age. FM was measured at 11, 13 and 15 years and FM index (FMI) calculated as FM/height((x)). Longitudinal models were adjusted for dietary misreporting, physical activity and maternal factors. RESULTS: DP z-scores at all ages were positively associated with later FMI. A 1 s.d. unit increase in DP z-score was longitudinally associated with an average increase in FMI z-score of 0.04 s.d. units (95% confidence interval (CI), 0.01-0.07). For each 1 s.d. unit increase in DP z-score, the odds of being in the highest quintile for FMI (as a marker of excess adiposity) increased by 13% (95% CI, 1-27%). CONCLUSIONS: Dietary habits during childhood are associated with increased adiposity in adolescence, with specific implications for dietary energy density, fat and fibre intake. Improving diet quality may reduce the risk of obesity in young people.